Pemberdayaan Masyarakat Berbasis Ekonomi Kreatif dalam Meningkatkan Kemandirian Ekonomi Masyarakat Desa Parsalakan Angkola Barat Tapanuli Selatan - Yusuf Pathuansyah; Rizky Mery Octavianna; Noni Paisah (Jurnal Transformasi Pendidikan Indonesia, 2024)
Efforts to empower the people of Parsalakan Village, West Angkola District, South Tapanuli have provided knowledge, awareness and full power to the people of Parsalakan Village, West Angkola District, South Tapanuli in achieving change to become a more independent society. This research uses qualitative methods, where the researcher is the key instrument. The data collection technique is carried out using triangulation (combination), the data is inductive, and the research results are focused on the core or meaning and not globally. Based on the place of implementation, this research is field research and literature. If viewed based on its use, this research is applied research. The research results show that creative economy-based community empowerment activities have gone through: 1) The creative economy-based community empowerment process is carried out through activities for making creative economy products in Parsalakan Village, West Angkola District, South Tapanuli, which includes implementation stages. 2) There is potential for natural resources, human resources and business potential in Parsalakan Village, West Angkola District, South Tapanuli, proven that the community is able to utilize and develop local potential. 3) By forming community groups, it will be easier to mobilize community empowerment, such as fishermen groups, GAPoktan, and others. 4) Community participation occurs by providing awareness. 5) Training has been provided, even in 1 year 4-5 times training. The hope is that after receiving training the results can be developed with their group friends.